EFFECT OF DIETARY BANANA PSEUDO-STEM SIMPLICIA, COMMERCIAL VACCINE, AND THEIR COMBINATION ON THE GROWTH, HEALTH STATUS, AND IMMUNITY PERFORMANCE OF NILE TILAPIA AGAINST Aeromonas hydrophila - Wahjuningrum, Dinamella; Ramadhina, Erina Tri; Nuryati, Sri; Rizkiyanti, Ita; Abdullah, Taufiq (Indonesian Aquaculture Journal, 2025)
The sustainability of Nile tilapia production faces challenges from motile Aeromonas septicemia (MAS), caused by Aeromonas hydrophila. The use of antibiotics to control MAS has negative impacts on aquatic environments and consumer health. As alternatives, plant-based treatments and vaccination have been increasingly applied to replace antibiotics. This study aimed to evaluate the effects of banana pseudo-stem (BS), a commercial vaccine (CV), and their combination (BS+CV) on the growth, health status, and immune performance of Nile tilapia against A. hydrophila. A completely randomized design was used with five treatments: a negative control (C−), a positive control (C+), BS, CV, and BS+CV—each coated onto feed. Each treatment had three replications. Fish were reared in 36-L aquaria for 42 days to evaluate growth performance, followed by a challenge test with A. hydrophila on day 43. Survival was monitored for 14 days post-challenge. The highest growth performance was observed in the BS treatment compared to the other treatments. Meanwhile, survival rate (SR) and feed conversion ratio (FCR) did not show significant differences (P>0.05) among treatments. After the challenge, survival rates in the BS (96.67%), CV (73.33%), and BS+CV (76.67%) groups were significantly higher (P<0.05) than in the positive control group (50.00%). The BS group did not differ significantly (P>0.05) from the negative control group (100.00%). These findings indicate that BS, CV, and BS+CV enhance the immune response of Nile tilapia against A. hydrophila, with BS being the most effective in improving both growth and disease resistance.